The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s0104-66322010000300008
|View full text |Cite
|
Sign up to set email alerts
|

An algebraic approach for simultaneous solution of process and molecular design problems

Abstract: -The property integration framework has allowed for simultaneous representation of processes and products from a properties perspective and thereby established a link between molecular and process design problems. The simultaneous approach involves solving two reverse problems. The first reverse problem identifies the property targets corresponding to the desired process performance. The second reverse problem is the reverse of a property prediction problem, which identifies the molecular structures that match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…These targets were then used in a computeraided molecular design (CAMD) approach to find molecules that (nearly) achieve these targets. Within this class of approaches, the CAMD step can be performed via the use of "molecular property clusters," 21 by using algebraic methods, 22 or molecular signatures. 23 In another method first proposed by Bardow et al, 24,25 continuous molecular targeting (CoMT), the continuous descriptors of an optimal (hypothetical) solvent, representing the parameters of the PC-SAFT equation of state, 26 were first determined based on process performance.…”
Section: Introductionmentioning
confidence: 99%
“…These targets were then used in a computeraided molecular design (CAMD) approach to find molecules that (nearly) achieve these targets. Within this class of approaches, the CAMD step can be performed via the use of "molecular property clusters," 21 by using algebraic methods, 22 or molecular signatures. 23 In another method first proposed by Bardow et al, 24,25 continuous molecular targeting (CoMT), the continuous descriptors of an optimal (hypothetical) solvent, representing the parameters of the PC-SAFT equation of state, 26 were first determined based on process performance.…”
Section: Introductionmentioning
confidence: 99%
“…Eljack and Eden 15 proposed a visual approach via property clusters and group contribution methods, and Eljack et al 16 reported a propertybased approach for simultaneous process and molecular design. Bommareddy et al 17,18 proposed the use of property integration for process and molecular design, then Bommareddy et al 19 incorporated this approach to use signature descriptors. Chemmangattuvalappil et al 20 proposed a new algorithm for molecular design using new property operators, and Chemmangattuvalappil et al 21 used property clustering for process and product design.…”
Section: Introductionmentioning
confidence: 99%